Occupational Exposure to the Ugandan Research Strain (MR766) of Zika Virus. (25th October 2019) - Lichtenberger, Paola N; Ricciardi, Michael J; Solorzano, Dalhila; Raccamarich, Patricia; Leda, Ana; Sharkey, Mark; Watkins, David I; El Sahly, Hana; Rouphael, Nadine; Mulligan, Mark J; Doblecki-Lewis, Susanne; Stevenson, Mario; et al.
Abstract: A laboratory worker suffered an accidental needle-stick resulting in an exposure to the Ugandan strain (MR766) of Zika virus, which has rarely been studied in humans. We report the clinical presentation and outcomes, molecular and serological diagnostic results, and antibody response.